Desde el umbral: Perros del Titicaca. Breves notas etnográficas - Gerardo Fernández Juárez (Nuevo mundo - Mundos Nuevos, 2021)
This paper shows different ethnographic situations from the Aymara region of Lake Titicaca in Bolivia in which dogs, particularly black, act as protagonists of the threshold. The transit scenarios between the domestic and the wild; Health and illness; life and death, as well as the present and the past, acquire particular relevance for dogs. These dogs protect the cosmological doors, boundary spaces, and thresholds that the humans, souls, or ceremonial entities traverse in the Altiplano.